2020
DOI: 10.2147/ijnrd.s237527
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Supportive Treatment of IgA Nephropathy and Idiopathic Nephrotic Syndrome: How Useful are Omega-3 Polyunsaturated Fatty Acids?</p>

Abstract: IgA nephropathy (IgAN) is the most prevalent glomerular disease in young adults worldwide, while idiopathic nephrotic syndrome (INS) represents the most frequent manifestation of glomerular disease in childhood. Over the years, studies have speculated about the potential benefits of omega-3 polyunsaturated fatty acids (PUFAs) in improving morbidity in both forms of chronic kidney disease (CKD). The proposed mechanisms of action include reduction of proteinuria and modulation of dyslipidemia. Although in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…EPA competes with arachidonic acid to switch the synthesis pathway to promote the production of anti-inflammatory eicosanoids [77]. In addition, eicosanoids derived from O3FA have shown clinical benefits for cardiovascular disease, diabetes, and nephropathies due to their anti-inflammatory effects [77,78].…”
Section: Soluble Fiber and Omega-3 Fatty Acidsmentioning
confidence: 99%
“…EPA competes with arachidonic acid to switch the synthesis pathway to promote the production of anti-inflammatory eicosanoids [77]. In addition, eicosanoids derived from O3FA have shown clinical benefits for cardiovascular disease, diabetes, and nephropathies due to their anti-inflammatory effects [77,78].…”
Section: Soluble Fiber and Omega-3 Fatty Acidsmentioning
confidence: 99%
“…Additionally, sharing sharp objects was associated with a higher HIV/HBV co-infection rate (8.82%) compared to those who did not share (7.58%) (p = 0.15). or lower than reported percentages in different studies: 9.20% discovered by (Bittaye et al, 2019), 10.68% in Sokoto (Uchenna Iyioku Ugah et al, 2020), and 10.87% discovered by Demarchi et al (2022). However, our study's prevalence was higher than percentages reported in other regions, such as 3.6% reported by (Ihongbe et al, 2022) in Ogun State, 3.5% in Anyigba, Kogi State (Cornelius et al, 2019, Nigeria, and various other percentages ranging from 4.0% to 7.6% in different studies (Banik et al, 2022;Emeka et al, 2013;;Lawal et al, 2020;Nwankwo et al, 2012 andOdita et al, 2023).…”
Section: Resultsmentioning
confidence: 58%
“…In addition, although the efficacy of N-3 fatty acids was found to be lower in this study, it was superior to that of the placebo, especially when the proteinuria at the baseline was higher. N-3 fatty acids act on the renal inflammatory pathway to affect the level of glomerular proteinuria and regulate cholesterol and triglycerides to delay renal toxicity associated with dyslipidemia ( 26 ). Considering that N-3 fatty acids are essential fatty acids for the human body, long-term use of N-3 fatty acids is safer than other drugs; thus, it also has a certain value for treating IgA nephropathy.…”
Section: Discussionmentioning
confidence: 99%